2020
DOI: 10.1097/pas.0000000000001560
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Neuroendocrine Carcinomas of the Endometrium

Abstract: High-grade neuroendocrine carcinomas (NEC) of the endometrium are rare and account for <1% of all endometrial carcinomas. Both small cell neuroendocrine carcinoma (SCNEC) and large cell neuroendocrine carcinoma (LCNEC) morphologies have been reported. Little is known regarding the molecular features of endometrial NEC including how they compare to pulmonary NEC (the most common site for these neoplasms) and the more common endometrial carcinoma histotypes. In this study, we investigated the molecular altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 33 publications
4
30
1
Order By: Relevance
“…NEEC can be subdivided into small cell NEEC, characterized by hyperchromatic nuclei with high nuclear-to-cytoplasmic ratio, molding, and crushing artifacts, and large cell NEEC, characterized by appreciable cytoplasm, coarse nuclear chromatin with prominent nucleoli, and nested growth with peripheral nuclear palisading. Endometrial NEEC is often found admixed with other components, especially EEC [ 66 ]. The prognosis of gynecological NEECs is described as poor [ 67 ].…”
Section: Neuroendocrine Carcinoma (Neec)mentioning
confidence: 99%
See 1 more Smart Citation
“…NEEC can be subdivided into small cell NEEC, characterized by hyperchromatic nuclei with high nuclear-to-cytoplasmic ratio, molding, and crushing artifacts, and large cell NEEC, characterized by appreciable cytoplasm, coarse nuclear chromatin with prominent nucleoli, and nested growth with peripheral nuclear palisading. Endometrial NEEC is often found admixed with other components, especially EEC [ 66 ]. The prognosis of gynecological NEECs is described as poor [ 67 ].…”
Section: Neuroendocrine Carcinoma (Neec)mentioning
confidence: 99%
“…A recent study showed that all 4 TCGA groups were represented in a cohort of 14 NEECs (4 pure and 10 admixed with a second component) [ 66 ]. The most represented was the MMRd group, which accounted for more than 40% of cases; this percentage was consistent with previously published data [ 66 , 68 ]. Interestingly, all MMRd NEECs were mixed EEC/NEEC (except for one case that was UCS with a NEEC component).…”
Section: Neuroendocrine Carcinoma (Neec)mentioning
confidence: 99%
“…Additionally, both cervical and endometrial neuroendocrine carcinomas have not been reported to harbor inactivating SMARCA4 mutations. In the case of endometrial neuroendocrine carcinomas, nearly 50% are associated with mismatch repair deficiency/microsatellite instability 47,48 …”
Section: Section 1: Smarc‐deficient Uterine Sarcoma (Sdus)mentioning
confidence: 99%
“…4 These neoplasms are either "pure" LCNEC or mixed with other histologic components. [5][6][7][9][10][11][12][13][14][15][16][17][18][19] Among other histologic components of endometrial LCNEC, endometrioid carcinoma is the most common histologic type, followed by serous carcinoma. Based on prior reports and our case studies, the most common clinical symptoms are postmenopausal or perimenopausal vaginal bleeding and/or abnormal vaginal discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Ariura et al 19 also reported identical alterations in PTEN, PIK3CA and FGFR3 in the endocrine and LCNEC components of NEC. Howitt et al 18 reported that 50% of endometrial NECs were ultramutated or hypermutated, which is more representative of other histologic types of endometrial carcinoma than canonical small cell carcinoma of the lung. Such observations suggest that NEC may arise from adenocarcinoma via a "dedifferentiation process".…”
Section: Discussionmentioning
confidence: 99%